When I lived with bats - McNulty, Faith; Shiffman, Lena (New York : Scholastic, 1998)
A girl describes how she spent a summer observing the bats around and inside her house and what she discovered about their characteristics and behavior.
"Cartwheel books."
Keywords: Bats -- Juvenile literature; Bats